2020
DOI: 10.1155/2020/4785759
|View full text |Cite
|
Sign up to set email alerts
|

Immune Thrombocytopenic Purpura (ITP) as an Uncommon Extraintestinal Complication of Crohn’s Disease: Case Vignette and Systematic Literature Review

Abstract: While the association of immune thrombocytopenic purpura (ITP) and inflammatory bowel disease (IBD) has been described in a few case reports, management of ITP as an extraintestinal manifestation of Crohn’s disease (CD) is less studied. There are approximately a dozen cases describing the management of patients dually diagnosed with CD/ITP. Previous reports postulated that the mechanism of ITP in CD was through the presence of circulating immune complexes in the serum and antigenic mimicry due to increased muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The presence of immune thrombocytopenic purpura (ITP) in patients with IBD has been described in a limited number of cases. 28 Researchers support the theory of anti-genic mimicry between platelet surface and luminal antigens, thus creating a common immune-mediated pathway to mucosal inflammation and platelet destruction. Studies have shown increased levels of T-helper 1 and CD4 cells.…”
Section: Immune Thrombocytopenic Purpuramentioning
confidence: 97%
“…The presence of immune thrombocytopenic purpura (ITP) in patients with IBD has been described in a limited number of cases. 28 Researchers support the theory of anti-genic mimicry between platelet surface and luminal antigens, thus creating a common immune-mediated pathway to mucosal inflammation and platelet destruction. Studies have shown increased levels of T-helper 1 and CD4 cells.…”
Section: Immune Thrombocytopenic Purpuramentioning
confidence: 97%
“…In patients with UC, immune complexes escape from the gut to the circulating blood due to increased mucosal permeability during disease activity. 24 They cross-react with the platelet surface antigens, which carry similar peptides to bacterial glycoproteins in the gut and, subsequently, result in ITP. 24 Moreover, the autoreactive T-cells secrete eosinophilopoietic cytokines that promote eosinophils' survival, enhance their activity, and hinder their suppressive regulatory mechanisms.…”
Section: Implications Of Clinical Practicementioning
confidence: 99%
“…24 They cross-react with the platelet surface antigens, which carry similar peptides to bacterial glycoproteins in the gut and, subsequently, result in ITP. 24 Moreover, the autoreactive T-cells secrete eosinophilopoietic cytokines that promote eosinophils' survival, enhance their activity, and hinder their suppressive regulatory mechanisms. 20,21 Colectomy, therefore, would stop these pathogenic mechanisms and subsequently prevent platelets destruction and hypereosinophilia.…”
Section: Implications Of Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Immune thrombocytopenic purpura (ITP) is a rare EIM of IBD, commonly associated with UC [3]. ITP is characterized by the presence of autoantibodies against platelet membrane antigens, leading to immune-mediated destruction of platelets [4]. The pathogenesis of the association between IBD and ITP is explained by the mimicry between the luminal mucosa and platelet membrane antigens, leading to immunogenic activation that favors platelet destruction in the spleen [5].…”
Section: Introductionmentioning
confidence: 99%